Retrotransposon activation during Drosophila metamorphosis conditions adult antiviral responses. - Wang, L.; Tracy, L.; Su, W.; Yang, F.; Feng, Y.; Silverman, N.; Zhang, Z.Z.Z. (Nature Genetics, 2022)
Retrotransposons are one type of mobile genetic element that abundantly reside in the genomes of nearly all animals. Their uncontrolled activation is linked to sterility, cancer and other pathologies, thereby being largely considered detrimental. Here we report that, within a specific time window of development, retrotransposon activation can license the host's immune system for future antiviral responses. We found that the mdg4 (also known as Gypsy) retrotransposon selectively becomes active during metamorphosis at the Drosophila pupal stage. At this stage, mdg4 activation educates the host's innate immune system by inducing the systemic antiviral function of the nuclear factor-?B protein Relish in a dSTING-dependent manner. Consequently, adult flies with mdg4, Relish or dSTING silenced at the pupal stage are unable to clear exogenous viruses and succumb to viral infection. Altogether, our data reveal that hosts can establish a protective antiviral response that endows a long-term benefit in pathogen warfare due to the developmental activation of mobile genetic elements.